Pharmacology of spinal interventions: review of agents used in spine pain procedures - Torralba, Ericson John V.; Short, Robert F.; Travers, Jeffrey B.; Mathis, John M. (Frontiers in Pain Research, 2024)
Spine procedures are commonly performed to diagnose and treat various spinal conditions, ranging from degenerative disc disease to vertebral fractures. These procedures often involve the use of pharmaceutical agents to enhance the efficacy of the intervention and improve patient outcomes. This review provides an overview of the pharmaceuticals commonly utilized in spine procedures, including corticosteroids, anesthetics, antibiotics, radiographic contrast, neurolytic agents, and materials used in kyphoplasty and vertebroplasty. This review summarizes the utilization of these pharmaceutical agents in spine procedures in an effort to optimize patient outcomes. Understanding the pharmacological properties and appropriate uses of these pharmaceuticals is essential for interventionalist and healthcare providers involved in the care of patients undergoing spinal interventions.